2012
DOI: 10.1016/j.euroecorev.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Are income and consumption taxes ever really equivalent? Evidence from a real-effort experiment with real goods

Abstract: The public finance literature demonstrates the equivalence between consumption and labor income (wage) taxes. We construct an environment in which individuals make real labor-leisure choices and spend their earned income on real goods. We use this experimental framework to test whether a labor income tax and an equivalent consumption tax lead to an identical labor-leisure allocation. Despite controlling for subjects' work ability and inherent labor-leisure preferences and not allowing for saving, subjects redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 28 publications
5
70
0
Order By: Relevance
“…First, previous research demonstrates that taxes have a larger effect when more salient (e.g., Chetty et al, 2009;Blumkin et al, 2012), typical of a focusing illusion where making any attribute particularly salient leads that attitude to exert an outsized influence on decision-making (Kahneman et al, 2006). In our experiment, taxes are made explicit at the very moment that workers choose their labor supply decision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, previous research demonstrates that taxes have a larger effect when more salient (e.g., Chetty et al, 2009;Blumkin et al, 2012), typical of a focusing illusion where making any attribute particularly salient leads that attitude to exert an outsized influence on decision-making (Kahneman et al, 2006). In our experiment, taxes are made explicit at the very moment that workers choose their labor supply decision.…”
Section: Discussionmentioning
confidence: 99%
“…Field results on tax salience demonstrate that individuals respond less to a tax when the tax is less explicit Finkelstein, 2009;Cabral and Hoxby, 2012;Jones, 2012). Recent laboratory research has supported the claim that individuals respond more to taxes that are more salient (e.g., Sausgruber and Tyran, 2005;Blumkin et al, 2012), and increases in income taxes are often less salient than equivalent decreases in wages. found that laboratory workers who were paid the same net wage worked harder and longer when they faced higher gross wages and higher tax rates: a result they called "net wage illusion" since workers behaved as though their net wage was higher because their gross wage was higher.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…An overreaction to prices is plausible if prices are more salient than nominal income. The importance of salience effects is documented in Chetty et al (2009), Blumkin et al (2012), and Finkelstein (2009 who provide evidence that consumers fail to sufficiently take into account less salient aspects in decision making. 3 Income is usually paid monthly and changes only infrequently.…”
Section: Introductionmentioning
confidence: 99%
“…Blumkin et al 2012 for a recent example which handles payment in a similar manner). Additionally, this payment method, along with the fact that subjects were not informed about the prevailing tax rate until the start of a round, avoids adding an intertemporal component to our experiment.…”
Section: Paymentmentioning
confidence: 99%